Parenting behavior and psychodynamic conflicts: Cross-sectional findings in a normative sample of adolescents and their parents. Issue 4 (2nd October 2021) - Akın, Aslı; Seiffge-Krenke, Inge; Obbarius, Alexander; Reitzle, Matthias; Sarrar, Lea
Abstract: The present study aims at determining the associations between various dimensions of parenting behavior and the predominance of psychodynamic conflicts. Psychodynamic conflicts are described as non-integrated, temporally persistent, contradictory perspectives of experience and action. The OPD Conflict Questionnaires for children and adults, as well as both the children's and parents' versions of the Zurich Brief Questionnaire for the Assessment of Parental Behaviors were used to assess psychodynamic conflicts and parenting behavior in a sample comprising 221 healthy adolescents, 132 mothers, and 76 fathers, respectively. We found that a) controlling parenting behavior decreases with increasing age of adolescents, that b) girls tend to have passive identity and self-worth conflicts, while boys more often have an active oedipal conflict, and that c) girls perceive more maternal warmth and support than boys do. While perceived parental psychological control, especially by mothers, was positively associated with psychodynamic conflicts in adolescents, parental warmth and behavioral control were negatively associated with psychodynamic conflicts in adolescents. The reports from the parents on their parenting dimensions were partly associated with their own psychodynamic conflicts as well as with the conflicts of both their partners and children, respectively. Our findings show that psychodynamic conflicts and psychologically controlling parenting behavior do not only exist in families in which members suffer from mental illnesses but also in "healthy" families. Furthermore, the strong interrelations between psychodynamic conflicts and perceived parenting behavior of both parents and adolescents underline the need for integrated family therapy when adolescents become mentally ill.